Navigating Business Ethics in Local Environments: A Study on Organizational Care - Saeed, Amira R. Patel; Zara E. (Journal of Computer Engineering, 2024)
This study examines local communities’ lived experiences and organizations’ care-giving processes regarding four oil and gas projects deployed in three countries. Analyzing the empirical data through the lens of ethics of care reveals that, together with mature justice, the inclination to care conceived at the focal organization creates an ethical culture encouraging caring activities by individuals at the local level. Through close communications with communities, project decision makers at the local level recognize the demanded care of local communities and develop organizations’ caring capacity. The empirical analysis revealed that the care-giving process can also be influenced by the power dynamics of the network of stakeholders. This research emphasizes on the success of a bottom-up approach in caring for local communities, and sheds light on the capability of large organizations in giving care to their distal stakeholders by adopting this approach. Furthermore, it indicates that justice and care both have some useful characteristics and are complementary but, most importantly, are socially constructed and not mutually exclusive.